Childbirth Fear in Primigravida Pregnant Women: Exploring the Role of Resilience, Social Support, and Childbirth Self-Efficacy - Eva Nur Rachmah; Evy Tjahjono; Monique Elizabeth Sukamto (Journal of Educational, Health and Community Psychology, 2026)
This study examined a structural model of fear of childbirth (FOC) among primigravida pregnant women by investigating the roles of resilience and perceived social support, with childbirth self-efficacy as a mediating variable. Fear of childbirth is a significant psychological concern that may negatively affect maternal well-being and childbirth outcomes. A cross-sectional quantitative design using Structural Equation Modeling (SEM) was employed. Participants consisted of 420 primigravida pregnant women recruited from the Gerbangkertasusila region in East Java, Indonesia, through convenience sampling. The proposed model demonstrated a good fit to the data (CFI = 0.967, TLI = 0.957, RMSEA = 0.055, SRMR = 0.063). Childbirth self-efficacy showed a significant negative direct effect on fear of childbirth (β = −0.503, p < 0.001), indicating that higher self-efficacy was associated with lower fear levels. Social support and resilience did not show significant direct effects on fear of childbirth. However, social support had a significant indirect effect on fear of childbirth through childbirth self-efficacy (β = 0.091, p < 0.01). These findings suggest that the influence of social support depends on how it shapes maternal confidence and perceived autonomy. The study highlights childbirth self-efficacy as a central psychological mechanism underlying fear of childbirth and emphasizes the importance of empowering antenatal support interventions.